Contextual Teaching and Learning Model in the Speaking Skill Textbook for the Arabic Language Education Department - Miftahul Mufid; Isnainiyah; Nurul Ainiy (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: The Contextual Teaching and Learning (CTL) model is a holistic and natural instructional approach that enables students to learn educational content in a contextualized manner, linking it to their personal and social daily lives. Through this model, students actively construct knowledge based on their experiences and interactions. In this study, the CTL model is implemented through the Speech Skills textbook used in the Department of Arabic Language Education at the Islamic University of Malang, Indonesia. Methodology: This research employs a qualitative approach with a case study design, aiming to explore the implementation of the CTL model in the textbook and its contribution to improving students’ speaking competencies. Data were collected through observation, interviews, and documentation, focusing on the structure, content, and pedagogical strategies embedded in the textbook. Findings: The findings reveal that the CTL model in the Speech Skills textbook was not merely theoretical but practical and student-centered. It encourages independent learning, facilitates real-life language use, and enhances students’ motivation to express themselves fluently. The textbook integrates authentic topics and tasks related to students’ daily lives, making learning more meaningful, contextual, and communicative. This approach ultimately supports the development of learners’ linguistic proficiency, critical thinking, and social awareness, which are essential in mastering Arabic speaking skills. Implications/Novel Contribution: The study uniquely highlighted the significance of CTL model in speech skill development and its role in students speaking ability. Hence, providing several key policy recommendations and future research directions.